Relationships Across the Divide: An Instigator of Transformation - O'Keefe, Theresa (Studies in Christian-Jewish Relations, 2011)
Much has been accomplished on formal levels to improve relations among Christians and Jews over the past fifty years. However, the same advances have not been made on the local level, between members of Christian and Jewish congregations. The challenge is to find an educational model that best serves adult congregants so as to lead to a transformed relationship among Christian and Jewish congregants and con-gregations. I argue that building relationships among individual Christians and Jews should be central to an educational agenda for members of local congregations. Interfaith relationships serve as a motivator of care and understanding for congre-gants, just as they do for leaders in dialogue. Direct engagement between congregants results in greater self-awareness and commitment to improve relations between the two religious communities.